Analysis of the effect of bedding attitude on relaxation deformation characteristics of the surrounding rock of an underground powerhouse in a layered rock mass. Issue 7 (October 2021) - Zhang, Qiang; Liu, Jiahui; Pi, Jin; Wang, Yanbing; Wang, Yujie
Abstract: To study the stability of an underground powerhouse in layered rock mass, a series of numerical simulations was conducted using three-dimensional distinct element code to investigate the effect of bedding attitude on the relaxation deformation characteristics of the surrounding rock of an underground powerhouse. The results showed that when the bedding dip angle was less than 30°, the maximum deformation of the surrounding rock occurred at the arch crown and bottom plate. However, when the dip angle was greater than 60°, the maximum deformation occurred at the side wall. Under the same conditions, with the increase in dip angle, the maximum deformation of the surrounding rock and the depth of the relaxation deformation zone (RDZ) increased first and then decreased, and their peak values were observed when the dip angle reached 60°–70°. With the increase in the angle between the bedding strike and longitudinal axis of the cavern, the maximum deformation and depth of the RDZ decreased gradually and stabilized when the angle was greater than the threshold. For the steeply inclined layered rock mass, when designing the underground powerhouse, the angle between the bedding strike and longitudinal axis of the cavern should not be less than 60°.